Request for Derivation of Investigation Report of Suspect by Legal Counsel during Investigation Stage - Abdillah, Irvan (Strata Law Review, 2025)
The purpose of this research is to know, analyze and clarify the rights of the suspect, especially in Article 72 of the Criminal Procedure Code regarding the right of the suspect or his legal counsel to obtain a derivative of the minutes of the examination, a derivative of the minutes of the examination according to Article 72 of the Criminal Procedure Code which is for the purpose of defending the suspect. It is very necessary to confirm the rights of the suspect in Article 72 of the Criminal Procedure Code, namely in terms of submitting a derivative of the minutes of the examination. This research employs a normative legal research method. Using both a statutory and conceptual approach. Basically, the derivative of the minutes of examination is useful for the defense of the suspect. It is hoped that for the future draft of the Criminal Procedure Code, especially Article 72 of the Criminal Procedure Code regarding the right of the suspect or his legal counsel to obtain a derivative of the minutes of the examination, the formulators will add the word mandatory considering the importance of the derivative of the minutes of the examination in a legal system that adheres to the principle of Accusatoir. Article 72 of the Criminal Procedure Code requires sanctions if the article is not implemented in the investigation; hence, the immediacy of the derivative of the minutes is critical in ensuring the suspect's legal rights.